THE PROFESSIONAL PROFICIENCY OF PHYSICAL EDUCATION INSTRUCTORS IN FINLAND (International conference on multidisciplinary science, 2023)
This scholarly exposition delves into the proficiency of Physical Education (PE) instructors in Finland, scrutinizing the intricacies of the educational framework, professional advancement, and the consequential influence of these variables on the caliber of PE pedagogy. Renowned for its educational eminence, Finland’s educational system serves as a noteworthy backdrop to discern the competency of PE teachers, thereby offering discerning perspectives on the determinants underpinning the triumph of physical education within the nation. Leveraging extant scholarly works, educational directives, and interviews with PE pedagogues, the investigation dissects the multifaceted facets constituting teacher proficiency.